An Activated Potassium Phosphate Fertilizer Solution for Stimulating the Growth of Agricultural Plants - Belov, Sergej V.; Danyleiko, Yurij K.; Glinushkin, Alexey P.; Kalinitchenko, Valery P.; Egorov, Alexey V.; Sidorov, Vladimir A.; Konchekov, Evgeny M.; Gudkov, Sergey V.; Dorokhov, Aleksey S.; Lobachevsky, Yakov P.; Izmailov, Andrey Yu (Frontiers in Physics, 2021)
This study aimed to develop a sustainable industrial chemical engineering technology to improve the interaction between technology, plants, and soil in agriculture. The signaling crosstalk between H2O2 and NO and that between H2O2 and Ca2+ influence plant developmental and physiological processes. Many promising technologies for crop stimulation and protection are based on a thorough study of the environmental impact of various physical factors. A low-temperature, high-frequency plasma was generated via cathode high-frequency glow discharge and used for the electrolysis of an aqueous solution of a low concentration of the strong electrolyte KH2PO4, with an electrolysis-activated solution named Plasmolite. The Plasmolite solution yielded a Raman (red) scattering spectrum with a maximum at 1,640 cm−1, which was associated with hydrogen atom vibrations, and other bands at 875, 930, 1,050, and 1,123 cm−1, which were associated with the aqueous electrolyte solution plasma treatment. Based on the goal of producing an optimal H2O2 concentration of 100 μM, two types of seeds were exposed to a Plasmolite-based 2 × 10–5 M KH2PO4 solution moisturizing medium for three days. Approximately 92% of the spring spelled seeds (grade “Gremme”) that were exposed to this test solution sprouted, compared with 76% of the seeds exposed to a control solution. The spring rye seeds (grade “Onokhoyskaya”) that were exposed to the test solution sprouted at a rate of 90% compared with 75% in the control. The percentage of seeds that sprouted with a root length of more than 6 mm was approximately 80% for the test solution, compared to 50% for the control. Based on these results, the use of Plasmolite is considered to be promising for the production of activated H2O2 for protecting plants and stimulating growth, particularly for enhancing the functions of K and P2O5 of fertilizers.